2020 FDA TIDES (Peptides and Oligonucleotides) Harvest - Al Musaimi, Othman (Pharmaceuticals (Basel), 2021)
2020 has been an extremely difficult and challenging year as a result of the coronavirus disease 2019 (COVID-19) pandemic and one in which most efforts have been channeled into tackling the global health crisis. The US Food and Drug Administration (FDA) has approved 53 new drug entities, six of which fall in the peptides and oligonucleotides (TIDES) category. The number of authorizations for these kinds of drugs has been similar to that of previous years, thereby reflecting the consolidation of the TIDES market. Here, the TIDES approved in 2020 are analyzed in terms of chemical structure, medical target, mode of action, and adverse effects.